2016
DOI: 10.1016/j.socscimed.2015.12.029
|View full text |Cite
|
Sign up to set email alerts
|

The physiological impacts of wealth shocks in late life: Evidence from the Great Recession

Abstract: Given documented links between individual socioeconomic status (SES) and health, it is likely that—in addition to its impacts on individuals’ wallets and bank accounts—the Great Recession also took a toll on individuals’ disease and mortality risk. Exploiting a quasi-natural experiment design, this study utilizes nationally representative, longitudinal data from the National Social Life, Health, and Aging Project (NSHAP) (2005-2011) (N=930) and individual fixed effects models to examine how household-level wea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
84
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(87 citation statements)
references
References 75 publications
(96 reference statements)
1
84
0
Order By: Relevance
“…For example, while education may improve health by improving health efficacy and human capital, income can afford individuals access to the material resources needed to afford healthy lifestyles and proper preventive health care (Elo 2009; Lynch 2006). Further, studies document a strong association between wealth and health, net of other indicators of SES (Robert and House 1996; Pollack et al 2007), with scholars hypothesizing that wealth may provide households with economic stability in times of diminished wages or economic distress (Boen and Yang 2016). For this reason, it is essential that studies of health include multiple measures of SES to fully capture the role of SES in affecting individual-level health and population-level health disparities (Braveman et al 2005).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, while education may improve health by improving health efficacy and human capital, income can afford individuals access to the material resources needed to afford healthy lifestyles and proper preventive health care (Elo 2009; Lynch 2006). Further, studies document a strong association between wealth and health, net of other indicators of SES (Robert and House 1996; Pollack et al 2007), with scholars hypothesizing that wealth may provide households with economic stability in times of diminished wages or economic distress (Boen and Yang 2016). For this reason, it is essential that studies of health include multiple measures of SES to fully capture the role of SES in affecting individual-level health and population-level health disparities (Braveman et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…For one, different components of SES may be more or less important for health at various life stages and, as a result, the associations between various components of SES and health may vary by age. For example, research finds that while income may best reflect the socioeconomic well-being of working-aged adults, wealth may have particularly strong associations with health indicators in later life, as individuals increasingly turn to their accumulated assets to support themselves and their families (Robert and House 1996; Boen and Yang 2016). In addition, similar to racial disparities in health, the magnitude of socioeconomic disparities in health may vary across the life course, as the advantages and disadvantages associated with the individual components of SES accumulate, diminish, or remain stable with age (Shuey and Willson 2008).…”
Section: Introductionmentioning
confidence: 99%
“…We use change in total household net worth to capture wealth losses that occur across much broader segments of the population. Several studies have examined wealth shock as any change in the wealth amount,9 10 12 but low-level change may not be truly ‘shocking’ and instead represent measurement error or planned dissaving 17. We derived the 75% negative wealth shock measure using known predictors of unplanned, sudden wealth loss to attempt to minimise exposure misclassification.…”
Section: Discussionmentioning
confidence: 99%
“…The stress pathway implies that a wealth shock induces psychological and physiological stress responses. For example, home and investment loss have been associated with adverse mental health outcomes,5–11 including depression, anxiety and psychological distress, while total wealth loss has been associated with elevated blood pressure and inflammation 12. The second pathway implies that wealth shock prompts decreased consumption of health-related goods and services.…”
Section: Introductionmentioning
confidence: 99%
“…Our current understanding of the relationship between socioeconomic status (SES) and obesity is largely based on education, occupation, and income, but for those entering middle adulthood (45 to 65 years old), wealth is a key indicator of SES and a correlate of health and obesity (1)(2)(3)(4). Hajat et al (1), for example, found that those in the lowest quintiles of wealth in their sample had a 40 to 89 percent higher risk of becoming obese than those in the highest quintiles.…”
Section: Introductionmentioning
confidence: 99%